Hero of two ages: Mohd Said Sulaiman as the first Malay autobiography editor - Hamdan, Rahimah; Md. Radzi, Shaiful Bahri (Canadian Center of Science and Education, 2014)
This paper discusses the role of an early 20th century Johore intellectual and early Malay autobiography editor named Mohd Said Sulaiman in linking the traditional to the modern era. Mohd Said’s prowess as a Johore Malay figure was not only due to the fact that he was an important individual in the government (being the Sultan’s private secretary) but that he was also a very prolific scholar in the field of Malay literature. He produced several Malay literary works, either in prose or poetry, culminating in the completion of the major task of introducing these works to Sultan Ibrahim of Johore, who finally decreed that Ibrahim Munsyi’s autobiography be printed and edited in a scholarly manner without altering its contents. Thus began Mohd Said Sulaiman’s journey as the link between the traditional era (the era of the manuscript) and the modern era (the printing press) until this work could continue in the form of the text as it is today. As a result, Kisah Pelayaran Muhammad Ibrahim Munsyi was successfully published for the first time in 1919. The Japanese Occupation of Malaya until 1945 resulted in the disappearance of the original manuscript on Ibrahim Munsyi. The only evidence of the existence of the early autobiography for the Malay community was Mohd Said Sulaiman’s publication in 1919. It is apparent that the contribution of the late Mohd Said also paved the way and provided useful input to the history of Johore and the West Coast of Peninsular Malaysia, which all along had only relied on the reports of British officials, which were slanted more towards 'white supremacy'. Indirectly, the complete works edited by him can promote the study of various disciplines such as social studies. Research has shown that Mohd Said Sulaiman is one of the greatest literary figures of Johore because of his far-sighted vision, which gained prominence for the Johore Government on the world stage.